The course of bronchial asthma associated with metabolic syndrome in children with different phenotypes depending on vitamin D3 level - T. L. Protsiuk; O. V. Herasymova; L. O. Protsiuk; N. M. Surkova (Zaporozhye State Medical University, 2018)
Abstract Objective: to establish specific features of BA course in children with various phenotypes on the background of metabolic syndrome, depending on serum vitamin D3 level. Subjects and methods. 106 children with BA participated in the study. 42 patients had BA associated with metabolic syndrome (MS), and 64 had BA with no MS. By the phenotype 61 (57.5 %) of patients had allergen-induced (allergic) asthma and 45 (42.5 %) - virus-induced (non-allergic) BA. The control group consisted of 44 children (the patients with MS and those without MS and BA), average age 15.5 ± 1.3 years. All the patients underwent a unified complex of diagnostic investigations: general physical examination, measurement of waist circumference and body mass index (BMI), clinical blood test, spirometry, lipid profile. Weight categories (normal weight, excess weight and obesity) were determined by percentiles (P) of BMI variation series with regard to age, as indicated in WHO recommendations. Serum 25(OH)D levels were determined by enzyme immunoassay. Vitamin D level ≥20 ng/ml was considered sufficient, 11-20 ng/ml - insufficient, ≤10 ng/ml - deficient. General and specific serum IgE levels were determined by enzyme immunoassay. The data obtained were processed with Statistica 8 program, P values of less than 0.05 were considered to indicate statistical significance. Results. In the group of patients with vitamin D3 level below 20 ng/ml, 19.5 % had controlled BA and 41.3 % - uncontrolled BA, while among the children with vitamin D level over 20 ng/ml, 30.4 % had controlled BA and 8.6 % - uncontrolled BA (χ2= 9.12, P < 0.05). Mean value of vitamin D3 concentration in the control group was significantly higher than in the patients with BA associated with MS and BA without MS (P < 0.05). The relationship between OW, obesity and atopy was confirmed by high serum level of sIgE antibodies in those weight categories. High sIgE levels to allergens from the pollen of meadow grass, weeds and trees, animal epithelium, household dust mite, food and fungal allergens were determined much more frequently in the children with OW and obesity than in those with NW. In the patients with BA associated with MS and vitamin D3 level below 20 ng/ml, FEV1 and FVLC values appeared to be significantly lower as compared to those with vitamin D3 level over 20 ng/ml (P = 0.002). Inverse relationship between the most important parameters of external respiration function and BMI was established: VLC (rxy = -0.45, P = 0.002), FVLC (rxy = -0.52, P = 0.001), FEV1 (rxy = -0.78, P = 0.000), respectively. Conclusions. The severity of BA as well as the degree of its control in the patients with different phenotypes was found to be influenced by both the presence of MS and vitamin D3 level. Therefore, vitamin D deficiency can be one of the risk factors of BA and MS development, and can affect the severity of both BA and MS course. Vitamin D3 deficiency and the presence of MS greatly influence FEV1, FVLC, PEF values, decreasing the indices of external respiration in children and leading to more severe obstruction.